2021
DOI: 10.1136/bjophthalmol-2020-318236
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvascular signs in COVID-19

Abstract: Background/aimsTo explore if retinal findings are associated with COVID-19 infection.MethodsIn this prospective cross-sectional study, we recruited participants positive for COVID-19 by nasopharyngeal swab, with no medical history. Subjects underwent retinal imaging with an automated imaging device (3D OCT-1 Maestro, Topcon, Tokyo, Japan) to obtain colour fundus photographs (CFP) and optical coherence tomographic (OCT) scans of the macula. Data on personal biodata, medical history and vital signs were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 32 publications
0
40
1
6
Order By: Relevance
“…The examination was performed about 16 days after diagnosis of COVID-19 with PCV. 35 The highest prevalence of retinal microvascular abnormalities was reported by Pereira et al in a series comprising 18 COVID-19 patients with severe infection. Seventeen patients (94.4%) require ICU stay and 77.8% received invasive mechanical ventilation.…”
Section: Retinal Features Related To Micro-vasculopathy In Case-seriesmentioning
confidence: 92%
See 2 more Smart Citations
“…The examination was performed about 16 days after diagnosis of COVID-19 with PCV. 35 The highest prevalence of retinal microvascular abnormalities was reported by Pereira et al in a series comprising 18 COVID-19 patients with severe infection. Seventeen patients (94.4%) require ICU stay and 77.8% received invasive mechanical ventilation.…”
Section: Retinal Features Related To Micro-vasculopathy In Case-seriesmentioning
confidence: 92%
“…Among cases-control studies and case series, 18 publications (10 case-control studies [17][18][19][20][21][22][23][24][25]30 and 9 case series 13,28,29,[31][32][33][34][35][36] ) reported on the presence or absence of retinal signs related to micro-vasculopathy. Among the 10 case-control studies, retinal signs were reported in 6, with frequency ranging from 0.01% to 20%.…”
Section: Summary Findings Of Retinal Features Related To Micro-vasculopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Карбоксипептидазният рецептор, свързан с ангиотензин-конвертиращия ензим (АСЕ2), като таргет за SARS-CoV-2 е обилно експресиран в ретината и хориоидеята. Регулираното понижаване на този ензим по време на вирусна инфекция може да обясни развитието на ретинална исхемия [5].…”
Section: обсъжданеunclassified
“…Проучване на Сим и сътр. върху 108 пациенти с положителни назофарингеални проби за SARS-CoV-2 открива, че 11.6% демонстрират ретинални изменения, включително микрохеморагии, тортуозитет на съдовете и влажни ексудати с хиперрефлективни плаки на границата между ганглийно-клетъчния и вътрешния плексиформeн слой, без връзка със симптоматичния или асимптоматичния клиничен ход на респираторното заболяване [5].…”
unclassified